Assessment of medication knowledge and adherence among patients under oral chronic medication treatment in community pharmacy settings - İZZETTİN, FIKRET VEHBI; OKUYAN, BETÜL; SANCAR, MESUT; Izzettin, Fikret Vehbi (My University, 2013)
Purpose This study aimed to determine whether there is a relationship between the lack of medication knowledge and the self-reported rates of patient medication adherence. Methods Patients eligible to participate in the study had been taking oral medication at least once daily over the course of a minimum of three consecutive months before recruitment to the study. All participants were older than 18 years. The level of each patient-s knowledge of his or her medication was randomly assessed by a trained fifth-year pharmacy student through an adapted questionnaire. In addition, patient adherence was evaluated via utilization of the Morisky Medication Adherence Scale. Results Of the 765 study participants (mean +/- SD age = 55.45 +/- 15.05 years, range = 2091 years, 56.2% women), 58.0% reported adherence to their medication regimen and 64.5% professed optimal knowledge of their medication. The mean duration of medication utilization was 26.77 +/- 40.62 months (range = 3504 years). A statistically significant correlation exists between the total medication knowledge score on the questionnaire and the level of medication adherence (r=0.964, p<0.001). Conclusion Improvement in the patient-s knowledge of medications taken would bear a positive effect on medication adherence. Copyright (c) 2012 John Wiley & Sons, Ltd.